Ambient air pollution, temperature and kawasaki disease in Shanghai, China. (November 2017) - Lin, Zhijing; Meng, Xia; Chen, Renjie; Huang, Guoying; Ma, Xiaojing; Chen, Jingjing; Huang, Min; Huang, Meirong; Gui, Yonghao; Chu, Chen; Liu, Fang; Kan, Haidong
Abstract: Kawasaki disease (KD) is a kind of pediatric vasculitis of unknown etiology which mainly affects the development of coronary artery aneurysms. Few studies have explored the potential environmental risk factors on KD incidence. We performed a time-series analysis to investigate the associations between air pollution and temperature and KD in Shanghai, China. We collected daily-hospitalized KD patients that were admitted in major pediatric specialty hospitals located in the urban areas of Shanghai from 2001 to 2010. The over-dispersed generalized additive model was used to estimate the effects of air pollutants on KD incidence on each day. Then, this model was combined with a distributed lag non-linear model to estimate the cumulative effects of temperature over a week. There were positive but statistically insignificant associations between three major air pollutants and KD incidence. The association between daily mean temperature and KD was generally J-shaped with higher risks on hot days. The cumulative relative risk of KD at extreme hot temperature (99th percentile, 32.4 °C) over a week was 1.91 [95% conﬁdence interval (CI): 1.13, 3.23], compared with the referent temperature (10.0 °C). This study suggested that a short-term exposure to high temperature may significantly increase the incidence of KD, and the evidence linking air pollution and KD incidence was limited. Graphical abstract: Highlights: Air pollutants were not significantly associated with Kawasaki disease (KD). The results suggested that high temperature might increase KD incidence. The curve for the association between daily temperature and KD was "J-shaped". The effects of temperature increased from lag 0 d–6 d, and then decreased. The daily temperature with minimum risk of KD was about 10.0 °C.